Learning English Through Online Classes: Advantages and Disadvantages - Qo’shaqova Umida Doniyorbek qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the process of learning English through online classes, its relevance, advantages, and disadvantages. In today’s global digital education environment, the necessity of learning foreign languages, especially English, is increasing. Online education provides flexibility, affordability, broad access to resources, and opportunities for independent learning. However, there are also drawbacks, such as technical issues, lack of live communication, and low motivation. The article evaluates the effectiveness of online education based on methodological approaches. Both qualitative and quantitative research methods were used to study the opinions of students and teachers, and key findings are presented. Analysis based on experiments, surveys, and interviews revealed that learning English successfully through online classes is possible, but it requires discipline, self-control, and proper technical conditions. This article provides useful methodological recommendations for students, teachers, and educational organizers.